Un examen del "examen filial": a propósito de las acusaciones contra el fundador del movimiento de Schoenstatt = Abweichender Titel: An Examination of the "Filial Examination" : with Regard to the Accusations Against the Founder of the Schoenstatt Movement - Serrano del Pozo, Ignacio (Cauriensia, 2025)
The purpose of this article is to analyse a piece of spirituality that has recently been at the centre of controversy: the so-called "filial examination" or Kindesexamen that the founder of the Schoenstatt Apostolic Movement was carrying out within one of his foundations. This act has come to public light due to the accusations that the Church historian Alexandra von Teuffenbach has directed against Josef Kentenich, for eventual abusive practices, abuse of power, and emotional manipulation, that he would have committed against a group of consecrated women in the late 1940s. My thesis is that the Kindesexamen that seems to condemn Kentenich, can also function as a small semi-open window that illuminates many of his most original intuitions in both religious and psychological fields: the richness of Therese of Lisieux's spirituality of the "little way", the relevance of second causes and the concrete link to a father figure on the natural plane, as well as the importance of recognizing our weaknesses and of sublimating sexuality as therapeutic-pastoral forms.